DelaySSAToolkit.jl: stochastic simulation of reaction systems with time delays in Julia - Fu, Xiaoming; Zhou, Xinyi; Gu, Dongyang; Cao, Zhixing; Grima, Ramon (Bioinformatics, 2022)
Abstract Summary DelaySSAToolkit.jl is a Julia package for modelling reaction systems with non-Markovian dynamics, specifically those with time delays. These delays implicitly capture multiple intermediate reaction steps and hence serve as an effective model reduction technique for complex systems in biology, chemistry, ecology and genetics. The package implements a variety of exact formulations of the delay stochastic simulation algorithm. Availability and implementation The source code and documentation of DelaySSAToolkit.jl are available at https://github.com/palmtree2013/DelaySSAToolkit.jl.